Tending fire - Pyne, Stephen J. (Island Press, 2004)
The wildfires that spread across Southern California in the fall of 2003 were devastating in their scale-twenty-two deaths, thousands of homes destroyed and many more threatened, hundreds of thousands of acres burned. What had gone wrong? And why, after years of discussion of fire policy, are some of America's most spectacular conflagrations arising now, and often not in a remote wilderness but close to large settlements? That is the opening to a brilliant discussion of the politics of fire by one of the country's most knowledgeable writers on the subject, Stephen J. Pyne. Once a fire fighter himself (for fifteen seasons, on the North Rim of the Grand Canyon) and now a professor at Arizona State University, Pyne gives us for the first time a book-length discussion of fire policy, of how we have come to this pass, and where we might go from here